Electric Car Penetration Potential in Indonesia - Kresno Budi Wicaksono; Atik Aprianingsih (Jurnal Penelitian Transportasi Darat, 2021)
ABSTRACTElectric Car Penetration Potential in Indonesia: Automotive industry is one of the pillars that support Gross Domestic Product(GDP) in Indonesia. Moreover, despite of the pandemic condition, unlike internal combustion engine car, the sales of electric car isfound to be increasing in Indonesia and global. This signs that there may be transformation in automotive industry towards electric car. To prepare for the transformation, company must be able to understand customer. Furthermore, this study was done to know the potential of electric car in Indonesia and provide suggestions to company in the industry by understanding the customers. As a result, company needs to comprehend the factors that influence purchase intention of electric car. was In this study, understanding those factors was done with Theory of Planned Behaviour(TPB). In addition, it was found that purchase intention of electric car(PI) is greatly influenced by attitude(AT). While attitude to purchase electric car(AT) is greatly influenced by environment value. To sum up, this study showed that electric car has big growth potential in Indonesia. It is also showing the factors that influence customer purchase intention towards electric car in Indonesia. Keywords: electric car; growth potential; purchase intention; theory of planned behaviour.ABSTRAKOtomotif industri adalah salah satu penopang Produk Domestik Bruto(GDP) di Indonesia. Meskipun adanya pandemi, tidak seperti mobil pembakaran dalam, jumlah penjualan mobil listrik di Indonesia dan global meningkat. Ini adalah tanda yang memungkinkan perubahan pada industri otomotif ke arah mobil listrik. Oleh karena itu, perusahaan perlu mengetahui factor yang mempengaruhi niat untuk membeli mobil listrik. Analisa ini dilakukan untuk mengetahui potensi dari mobil listrik di Indonesia dan memberikan saran untuk perusahaan yang berada dalam industri dengan cara mengerti niat membeli. Mengetahui faktor yang mempengatuhi niat membeli dianalisa menggunakan Teori Perilaku Terencana(TPB). Hasil Analisa menunjukkan bahwa niat membeli mobil listrik(PI) sangat dipengaruhi oleh sikap(AT). Sedangkan sikap untuk membeli mobil listrik(AT) sangat dipengaruhi oleh nilai lingkungan(NV). Untuk merangkum, penelitian ini menunjukkan potensi pertumbuhan mobil listrik di Indonesia. Penelitian ini juga menunjukkan faktor yang mempengaruhi niat membeli mobil listrik di Indonesia.Kata Kunci: mobil listrik, niat membeli, potensi bertumbuh, teori perilaku terencana